2007
DOI: 10.1515/crelle.2007.014
|View full text |Cite
|
Sign up to set email alerts
|

A realization of the Hecke algebra on the space of period functions for Γ0 (n)

Abstract: Abstract. The standard realization of the Hecke algebra on classical holomorphic cusp forms and the corresponding period polynomials is well known. In this article we consider a nonstandard realization of the Hecke algebra on Maass cusp forms for the Hecke congruence subgroups Γ 0 (n). We show that the vector valued period functions derived recently by Hilgert, Mayer and Movasati as special eigenfunctions of the transfer operator for Γ 0 (n) are indeed related to the Maass cusp forms for these groups. This lea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 9 publications
(25 reference statements)
0
13
0
Order By: Relevance
“…For these finite index subgroups Deitmar and Hilgert [DH07] provided period functions for the Maass cusp forms of these groups also using representations. For the groups Γ 0 (N ), the combination of [HMM05] and [FMM07] shows a close relation between eigenfunctions of certain transfer operators and Maass cusp forms.…”
Section: Introduction and Statement Of Resultsmentioning
confidence: 99%
“…For these finite index subgroups Deitmar and Hilgert [DH07] provided period functions for the Maass cusp forms of these groups also using representations. For the groups Γ 0 (N ), the combination of [HMM05] and [FMM07] shows a close relation between eigenfunctions of certain transfer operators and Maass cusp forms.…”
Section: Introduction and Statement Of Resultsmentioning
confidence: 99%
“…In this limit the Hecke triangle group G q tends to the theta group Γ θ , generated by Sz = −1 z and T z = z + 2. This group is conjugate to the Hecke congruence subgroup Γ 0 (2), for which a transfer operator has been constructed in [7] and [5]. One should understand how these two different transfer operators are related to each other.…”
Section: The Selberg Zeta Function For Hecke Triangle Groupsmentioning
confidence: 99%
“…For χ being the trivial character, [34] and [14] showed that the map (25) f −1 = α s (g 3,1 )ϕ, ϕ = α s (g −1 3,1 )f −1 provides an isomorphism between the eigenfunctions of L slow,± The combination of [15,16,26,18,22] shows that (25) provides also an isomorphism for certain representations χ. These studies take advantage of the special structure of L fast,±…”
Section: 1mentioning
confidence: 99%